Paulo Freire’s legacy and critical pedagogy in dark times - Giroux, Henry (Studia Krytyczne/Critical Studies, 2025)
This article explores the enduring relevance of Paulo Freire’s critical pedagogy at a historical moment marked by rising authoritarianism and attacks on education as a critical and democratizing project. Freire’s philosophy, grounded in the belief that education is inherently political, emphasizes the role of theory, critical consciousness, and pedagogy as the practice of freedom in fostering a just and democratic society. Central to his vision is the understanding that power operates through cultural narratives, making it crucial to reclaim education as a space for shaping public consciousness. In an era where thinking is increasingly viewed as subversive, if not dangerous. Freire’s work serves as a call to resist the educational, cultural, and economic forces that perpetuate oppression and ignorance. The article highlights the need for educators to engage in dialogue, challenge oppressive power structures, take on the role of public intellectuals, build mass movements, and inspire students to become active agents of change. It underscores the importance of reclaiming education from neoliberal and fascist forces, advocating for a pedagogy that promotes democratic engagement, social justice, and the promise of a socialist democracy.